Performance analysis of thin surface course systems used in England: a novel approach based on viscous to elastic transition (VET) parameters - Khojinian, Arash (2020)
This research explores, investigates and assesses the performance of Thin Surface Course Systems (TSCS) used on the Strategic Road Network (SRN) in England. Fretting is acknowledged to be the main defect for TSCS. The key factors causing fretting on TSCS include poor designs, poor adhesion between the binder and the aggregate, poor compaction, aggressive scuffing by the traffic, bitumen ageing and effect of climatic conditions/laying season. The research reviews design specifications, installation, maintenance and asset management strategies of TSCS in the United Kingdom, Europe, United States, New Zealand and South Africa. This was carried out to ascertain best practice for TSCS worldwide and proffer effective solutions to improve performance and durability for use on the SRN. Findings from this research showed that most samples obtained from site had air void contents > 7%. Individual measurements of up to 19% were reported for some samples and the overall average air void content was 10.6%. The percentage of air void contents within the TSCS in England in comparison to other European countries is significantly higher. The study showed that the severity of fretting increases with high air void contents. High air void contents increase the permeability of the layer to air and water which makes the asphalt prone to stripping. This adversely impacts on the overall performance and durability of the TSCS. The research showed that TSCS samples major fretting had lower stiffness values. Further to this, findings showed that most TSCS observed showed signs of fretting and/or other defects after around five years of being in service. This is interestingly in line with the warranty period required within Highways England specifications. However, this contradicts previous studies carried out in England where it was concluded that if a TSCS has performed well within the first five years then it would continue to perform well for up to 10 years in service. The study showed that samples with higher texture depth were found to have higher air void content. This is thought to be due to the loss of surface aggregates. Higher texture depths are attributed to higher levels of fretting for TSCS. The research provided evidence showing low binder penetration values could result in increased fretting of TSCS. The study showed that TSCS laid in the winter had an increased chance of fretting in comparison to TSCS laid outside of this season. Based on the finding of this research study, it is therefore proposed to incorporate the following updates into Highways England (HE) design standard HD 30. This will help HE to understand the TSCS life expectancy performance within the network so that HE could move away from only 10-year cyclic TSCS replacement and develop a more intelligent Value Management approach based on the in-situ performance of TSCS rather than their age only. § The assessment of binder rheology should be included as part of the scheme level survey to ascertain pavement conditions. § Asphalt cores should be taken from locations representative of the site conditions. § The recovered binder should subsequently be subjected to rheological testing to BS EN 14770 by applying the following test conditions: Ø The test frequencies should include 0.4 Hz and 1.59 Hz; Ø The test temperatures should cover the minimum range from 0ºC to 60ºC; Ø The temperature and complex modulus at which the phase angle value equals 45 degrees (TVET and G*VET respectively) when tested at a frequency of 0.4 Hz must be reported. Plots of Viscous to Elastic Transition (VET) temperatures, TVET, against their respective complex stiffness modulus, G*VET, provide a useful tool for establishing how changes in the properties of bituminous materials may be associated with different levels of age hardening and/or distress levels (cracked or uncracked sites). The VET analysis developed in this study focuses on paving grade bitumen. Further studies and research focused on developing the VET analysis for polymer modified binders is recommended for future work. This is an important aspect in developing a comprehensive maintenance strategy for TSCS on the SRN.